First Report of Lasiodiplodia hormozganensis Causing Leaf Spot Disease on Areca catechu in China - Zhang, Chao (Plant disease, 2024)
The areca palm (Areca catechu L.) is one of the significant cash crops in Hainan Province (China), and a valuable tropical medicinal plant (Cao et al. 2020). In September 2020, spots were found on about 80% of the area of the leaves in a 1,000-acre plantation of areca palms in Haikou City, Hainan Province, and the average incidence was 25%. Initially, Elliptical or irregular dark brown spots appeared on the leaves, with an average size of about 1.5 cm2. With the further expansion of the disease, the spot turned light brown in the center with dark brown edges and a prominent yellow halo. Later stage of the disease, the spots became grayish-white in the center, with obvious whorls, on which many small black spots (pycnidia) were scattered. Eventually the leaves dried out. Ten leaves with typical symptoms were collected from the field. Lesion marginal tissues (5×5 mm2) were surfaced sterilized in 75% ethanol for 20 s, followed by 4 min in 1% NaClO, rinsed 3 times with sterile water, plated on PDA and incubated at 28 ℃. A fungus was isolated with a 98% isolation rate. This strain was named HNAC-5. Subcultures were 80 mm in diameter, white, villous, and neatly edged, after two days of incubation at 28 ℃ in dark. Pycnidia were solitary or clustered in stromata, with orifices that oozed black liquid. Conidiogenous cells were colorless and short cylindrical. Conidia unicellular, initially hyaline, aseptate, ellipsoid to ovoid with granular content, becoming pigmented, 1-septate with longitudinal striations, and measuring 20-31×10-13 μm (n=100). These morphological characteristics were similar to Lasiodiplodia spp. (Abdollahzadeh et al. 2010). The internal transcribed spacer region of rDNA, β-tubulin gene, and translation elongation gene were amplified using ITS1/ITS4, Bt2a/Bt2b, and EF1-728F/EF1-986R primers, respectively (Alves et al. 2008; Glass and Donaldson 1995; White et al. 1990). The resulting sequences were deposited in GenBank under accession numbers OR272043, OR282568, and OR282567. BLAST analysis showed that the three sequences of HNAC-5 were more than 99% similar to strain CBS 124709 of L. hormozganensis. Phylogenetic analysis was performed using the maximum likelihood method based on the three-gene combined dataset with MEGA 7.0 software. The results indicated that HNAC-5 was grouped in the same clade as other L. hormozganensis Abdollahzadeh, Zare & A.J.L. Phillips. Pathogenicity test was carried out on 15 healthy leaves by in vivo inoculation. Ten leaves were pricked with a sterile needle and divided into group 1 and 2. The remaining five uninjured leaves were group 3. Group 1 and 3 were inoculated with 5-mm-diameter mycelial plugs obtained from 3-day cultures, and group 2 treated with PDA plugs served as controls. Fifteen leaves were cultured at 28°C and 100% relative humidity. After 5 days, leaves of group 1 showed symptoms of the disease and on the tenth day showed the same symptoms as the initial onset of the disease in the field, while leaves of Group 2 and 3 showed no symptoms. Pathogenicity tests were conducted three times with the same results. L. hormozganensis was re-isolated from the inoculated symptomatic leaves, thus, Koch's postulates were confirmed. In China, L. hormozganensis has been reported to cause Bougainvillea spectabilis Willd. branch blight disease (Li et al. 2015), and Scaevola taccada (Gaertn.) Roxb. leaf spot disease (Zhang et al. 2020). To our knowledge, this is the first report of L. hormozganensis causing leaf spot disease on A. catechu in China